TWO NEW MEXICAN FLEAS OF THE GENUS OPISODASYS - DAMPF, ALFONSO (Laboratorio Zapata, CD MEXICO, DF, MEX, 1977)
Observations on Smerdalea horrescens, Tumecauda schaefferi and Dontonodus serraticornis are detailed Numerous variations, of specimens collected in Chiapas, from the original description are discussed
ANN MAG NAT HIST, LONDON
Keywords: NEW MEXICAN FLEAS, GENUS OPISODASYS; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL